Construction of an RNA-Binding Protein-Related Prognostic Model for Pancreatic Adenocarcinoma Based on TCGA and GTEx Databases - Wen, Xin; Shao, Zhiying; Chen, Shuyi; Wang, Wei; Wang, Yan; Jiang, Jinghua; Ma, Qinggong; Zhang, Longzhen (Frontiers in Genetics, 2021)
Abstract Background: Recently, RNA-binding proteins (RBPs) are reported to interact with target mRNA to regulate gene post-transcriptional expression and RBPs-mediated RNA modification can regulate the expression and function of proto-oncogenes and tumor suppressor genes. We systematically analyzed the expression of RBPs in pancreatic adenocarcinoma (PAAD) and constructed a RBPs associated prognostic risk model. Methods: Gene expression data of normal pancreatic samples as well as PAAD samples were downloaded from TCGA-PAAD and GTEx databases. Wilcoxon test and univariate Cox analysis were respectively applied to screen differential expression RBPs (DE-RBPs) and prognostic associated RBPs (pRBPs). Functional enrichment was analyzed by GO, KEGG and GSEA. Protein-protein interaction (PPI) network was constructed by STRING online database. Modeling RBPs were selected by multivariate Cox analysis. Kaplan-Meier survival and Cox analysis were applied to evaluate the effects of risk score on the overall survival of PAAD patients. ROC curves and validation cohort were applied to verify accuracy of the model. Nomogram was applied for predicting 1-, 3-, and 5-year overall survival (OS) of PAAD patients. At last, modeling RBPs were further analyzed to explore their differential expression, prognostic value as well as enrichment pathways in PAAD. Results: 453 RBPs were differentially expressed in normal and tumor samples, besides, 28 of which were prognostic associated. 453 DE-RBPs are functionally associated with ribosome, ribonuclease, spliceosome, et al. 8 RBPs (PABPC1, PRPF6, OAS1, RBM5, LSM12, IPO7, FXR1, RBM6) were identified to construct a prognostic risk model. Higher risk score not only predicted poor prognosis, but also was an independent poor prognostic indicator, which was verified by ROC curves and validation cohort. 8 modeling RBPs were confirmed to be significantly differentially expressed between normal and tumor samples from RNA and protein level. Besides, all of 8 RBPs were related with overall survival of PAAD patients. Conclusions: We successfully constructed a RBPs associated prognostic risk model in PAAD, which has potential clinical application prospect.